Air sampling procedures to evaluate microbial contamination: a comparison between active and passive methods in operating theatres - Napoli Christian; Marcotrigiano Vincenzo; Montagna Maria (BMC, 2012)
Abstract Background Since air can play a central role as a reservoir for microorganisms, in controlled environments such as operating theatres regular microbial monitoring is useful to measure air quality and identify critical situations. The aim of this study is to assess microbial contamination levels in operating theatres using both an active and a passive sampling method and then to assess if there is a correlation between the results of the two different sampling methods. Methods The study was performed in 32 turbulent air flow operating theatres of a University Hospital in Southern Italy. Active sampling was carried out using the Surface Air System and passive sampling with settle plates, in accordance with ISO 14698. The Total Viable Count (TVC) was evaluated at rest (in the morning before the beginning of surgical activity) and in operational (during surgery). Results The mean TVC at rest was 12.4 CFU/m3 and 722.5 CFU/m2/h for active and passive samplings respectively. The mean in operational TVC was 93.8 CFU/m3 (SD = 52.69; range = 22-256) and 10496.5 CFU/m2/h (SD = 7460.5; range = 1415.5-25479.7) for active and passive samplings respectively. Statistical analysis confirmed that the two methods correlate in a comparable way with the quality of air. Conclusion It is possible to conclude that both methods can be used for general monitoring of air contamination, such as routine surveillance programs. However, the choice must be made between one or the other to obtain specific information.